Netizens’ criticism of the government’s policy of “Meme Lockdown” during the Covid-19 pandemic; in Indonesia - Nuryana, Arief (International Journal of Humanities and Education Development (IJHED), 2024)
Indonesia was shocked by the presence of the Corona-19 virus in early 2020. Indonesian people respond to policies related to handling Covid-19 by closing access to their territory and making memes about corona. One of the interesting phenomena that occurred during the Covid-19 pandemic was the number of banners or memes posted in the alleys of human settlements in Indonesia, as a form of freedom of opinion to respond to the policies of the Indonesian Government Program in preventing the more massive spread of Covid-19. This study uses a qualitative descriptive method with the data used in this study is a language game on photo uploads in the form of memes on Instagram accounts. The selected data is adjusted to the research needs and is representative data. The purpose of this study is to describe language games with sound and semantic substitution in the Lockdown Policy Meme on the Covid-19 pandemic in Indonesia through Instagram. The results showed that in the field of phonology tended to use substitution language games, while in the field of semantics, the most widely used was homonym language games. The language game in memes during the Covid-19 Pandemic has not yet become a force affecting the policies implemented by the Indonesian government. In other words, the anxiety and uncertainty were hidden in the Corona meme only meant as a pun or humor that can make the reader smile a little and feel optimistic. This paper has implications for developing criticism of government policies via the internet as a medium of communication and for managing the balance between stability and change due to the Covid-19 pandemic in Indonesia. This paper fulfils an identified need to study how the internet as public sphere and medium to communicate about government policies in the current era.